A new approach to increasing the sensitivity of a gas sensor based on nanocrystalline silicon carbide films - Alexander Semenov; Denis Lubov (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
It was shown the possibility of increasing the sensitivity of a gas sensor based on nanocrystalline SiC films by using a scheme of a two-component sensing element, one of which is an n-nc-SiC film with electronic conductivity, and the second is an p-nc-SiC film with hole conductivity. It is shown that due to the opposite polarity of changes in resistance in the films under the simultaneous action of gases, the difference in relative resistance changes Δ in the n-nc-SiC and p-nc-SiC films will always be greater than in each film separately. The expediency of using a two-component sensing element of a gas sensor based on nc-SiC films with electron and hole conduction is shown.